The Design Enterprise: Rethinking the HCI Education Paradigm. - Faiola, Anthony (Design Issues)
The article recommends the adoption of the human-computer interaction (HCI) paradigm in the design curriculum aimed at teaching students the theory and best practice of design as a unified approach to knowledge management. This set up provides HCI discipline with a holistic approach and a broader research structure for building design knowledge. According to the author, the result is a framework for building design knowledge he refers to as Design Enterprise Model which extends the potential of HCI by emphasizing design as a unifier for managing knowledge domains of social science, design, business and computing.